Solving Singular Boundary Value Problems by Optimal Homotopy Asymptotic Method - S. Zuhra; S. Islam; M. Idrees; Rashid Nawaz; I. A. Shah; H. Ullah (International Journal of Differential Equations)
In this paper, optimal homotopy asymptotic method (OHAM) for the semianalytic solutions of nonlinear singular two-point boundary value problems has been applied to several problems. The solutions obtained by OHAM have been compared with the solutions of another method named as modified adomain decomposition (MADM). For testing the success of OHAM, both of the techniques have been analyzed against the exact solutions in all problems. It is proved by this paper that solutions of OHAM converge rapidly to the exact solution and show most effectiveness as compared to MADM.